Pengaruh Musik Dewasa pada Anak di Masa Pandemi - Wadu, Ryanty Putri Sari (Acintya, 2023)
This research examines explicitly adult music’s influence on children’s age at the Early Childhood Education level. The aim is to explore the theory of empathy in dealing with the impact of adult music on children during the Covid-19 pandemic. Where the problems faced by children related to the influence of adult music have influenced attitudes and behavior in everyday life. The method used to answer this problem is a participant. Researchers will be involved in conducting this research assistance. The study results show that parental empathy for children regarding adult music is essential to note. The condition of the covid-19 pandemic that forces children to spend a lot of time at home can cause children to feel bored quickly. Playing games and listening to adult music through gadgets owned by children can affect the development of psychology, behavior, and children’s partnerships if there is a lack of empathy and assistance from teachers at school. For this reason, compassion for children is essential in anticipating the harmful effects or influences of adult music that children listen to.Keywords: adult music, early childhood, empathy theory